Improving access for Urgent patients in Paediatric Neurology. Issue 1 (27th April 2017) - Mohamed, Khalid; Al Houri, Basema; Ibrahim, Khalid; M Khair, Abdulhafeez
Abstract : Referral and flow management is an important part of outpatient care; some patients require to be seen earlier than the next available appointment because of the nature of their presentation. We did not have a clear pathway for urgent patients being referred to our pediatric neurology service. When we reviewed this process in our Quality Improvement meeting we identified wide variation in the length of time such patients wait to be seen in clinic ranging from 2 to 11 weeks. Only 25% of patients identified as requiring urgent clinic appointments were seen in clinic within 2 weeks of triage. A new triage system was designed to identify urgent patients consistently. Three PDSA cycles tested change ideas: the first cycle tested introducing an urgent triage system, the second cycle tested giving urgent appointments directly from the triage decision utilising clinic cancellations and the third PDSA tested double notification of appointments for all urgent patients using the call centre and the neurology specialist nurses. After the third PDSA the percentage of patients seen within 2 weeks of triage increased from 25% to 80%. This change was tested across one clinic initially then tested across two more clinics. Our balancing measure, the third available routine appointment, remained stable indicating that improving access to emergency patients did not affect the waiting time for routine appointments. With good management of triage it is possible to improve access for urgent patients to be seen in clinic without impact on availability of routine appointments, resulting in better quality of care and patient satisfaction. Earlier appointments also improve clinic attendance rates.